PKA microdomain organisation and cAMP handling in healthy and dystrophic muscle in vivo. - Röder, I; Lissandron, V; Martin, J; Petersen, Y; Di Benedetto, G; Zaccolo, M; Rudolf, R (2009)
Signalling through protein kinase A (PKA) triggers a multitude of intracellular effects in response to a variety of extracellular stimuli. To guarantee signal specificity, different PKA isoforms are compartmentalised by Akinase anchoring proteins (AKAPs) into functional microdomains. By using genetically encoded fluorescent reporters of cAMP concentration that are targeted to the intracellular sites where PKA type I and PKA type II isoforms normally reside, we directly show for the first time spatially and functionally separate PKA microdomains in mouse skeletal muscle in vivo. The reporters localised into clearly distinct patterns within sarcomers, from where they could be displaced by means of AKAP disruptor peptides indicating the presence of disparate PKA type I and PKA type II anchor sites within skeletal muscle fibres. The functional relevance of such differential localisation was underscored by the finding of mutually exclusive and AKAP-dependent increases in [cAMP] in the PKA type I and PKA type II microdomains upon application of different cAMP agonists. Specifically, the sensors targeted to the PKA type II compartment responded only to norepinephrine, whereas those targeted to the PKA type I compartment responded only to alpha-calcitonin gene-related peptide. Notably, in dystrophic mdx mice the localisation pattern of the reporters was altered and the functional separation of the cAMP microdomains was abolished. In summary, our data indicate that an efficient organisation in microdomains of the cAMP/PKA pathway exists in the healthy skeletal muscle and that such organisation is subverted in dystrophic skeletal muscle.